On a possibility of the blocking of DNA specific recognition sites by hydrogen peroxide molecules during ion beam therapy - Zdorevskyi, O.O.; Piatnytskyi, D.V.; Volkov, S.N. (Доповіді НАН України, 2019)
Ion beam therapy is one of the most effective methods in treatment of cancer diseases. But up to nowadays, the mechanism of action of heavy ions on cancer cells has not been determined yet. Study of water fragmentation processes during ion beam therapy shows that, among different oxygen species, the significant amount of hydrogen peroxide molecules (H₂O₂) occurs in the сell medium. In the present work, the competitive interaction of H₂O₂ and H₂O molecules with specific DNA recognition sites is studied. Interaction energies of complexes consisting of nucleic bases (adenine, thymine, guanine, and cytosine) together with hydrogen peroxide and water molecules are calculated, using the method of atom-atom potential functions and density functional theory. The atomic groups of nuc leic bases that are more energetically favorable to be bound by hydrogen peroxide rather than by water molecule are found. Formation of such complexes can block the process of DNA replication on different stages and can be one of the mechanisms of ion beam action on cancer cells. Іонна терапія є одним з найефективніших методів лікування ракових захворювань. Але до цього часу механізм дії важких іонів на ракові клітини не визначений. Вивчення процесів фрагментації води під час іонної терапії показує, що серед великої кількості різних фрагментів у середовищі клітини утворюється значна концентрація молекул пероксиду водню (H₂O₂). У роботі наведено результати дослідження конкурентної взаємодії молекул H₂O₂ та H₂O із центрами специфічного розпізнавання ДНК. Енергії взаємодії комплексів, що складаються з нуклеїнових основ (аденін, тимін, гуанін і цитозин) разом з молекулами пероксиду водню і води, обчислені із застосуванням методу атом-атомних потенціальних функцій і теорії функціонала густини. Знайдено атомні групи нуклеїнових основ, які є більш енергетично вигідними для зв’язування з молекулами пероксиду водню, ніж з молекулами води. Утворення таких комплексів може блокувати процес реплікації ДНК на різних етапах і може бути одним з механізмів дії високоенергетичних іонів на ракові клітини. Ионная терапия является одним из наиболее эффективных методов лечения раковых заболеваний. Но до настоящего времени механизм действия тяжелых ионов на раковые клетки не установлен. Изучение процессов фрагментации воды при ионной терапии показывает, что среди большого количества различных фрагментов в клеточной среде образуется значительная концентрация молекул пероксида водорода (H₂O₂). В работе приведены результаты изучения конкурентного взаимодействия молекул H₂O₂ и H₂O с центрами специфического узнавания ДНК. Энергии взаимодействия комплексов, состоящих из нуклеиновых оснований (аденин, тимин, гуанин и цитозин) вместе с молекулами пероксида водорода и воды, рассчитаны с использованием метода атом-атомных потенциальных функций и теории функционала плотности. Найдены атомные группы нуклеиновых оснований, с которыми молекула пероксида водорода связывается значительно энергетически выгоднее, чем молекула воды. Образование таких комплексов может блокировать процесс репликации ДНК на разных стадиях и может быть одним из механизмов воздействия высокоэнергетических ионов на раковые клетки.